Entomology in the 21st Century: Tackling Insect Invasions, Promoting Advancements in Technology, and Using Effective Science Communication—2018 Student Debates. Issue 4 (3rd July 2019) - Parker, Casey; Bernaola, Lina; Lee, Benjamin W; Elmquist, Dane; Cohen, Abigail; Marshall, Adrian; Hepler, James; Pekarcik, Adrian; Justus, Emily; King, Kendall; Lee, Tae-Young; Esquivel, Carlos; et al.
Abstract: The 2018 student debates of the Entomological Society of America were held at the Joint Annual Meeting for the Entomological Societies of America, Canada, and British Columbia in Vancouver, BC. Three unbiased introductory speakers and six debate teams discussed and debated topics under the theme 'Entomology in the 21st Century: Tackling Insect Invasions, Promoting Advancements in Technology, and Using Effective Science Communication'. This year's debate topics included: 1) What is the most harmful invasive insect species in the world? 2) How can scientists diffuse the stigma or scare factor surrounding issues that become controversial such as genetically modified organisms, agricultural biotechnological developments, or pesticide chemicals? 3) What new/emerging technologies have the potential to revolutionize entomology (other than Clustered Regularly Interspaced Short Palindromic Repeats)? Introductory speakers and debate teams spent approximately 9 mo preparing their statements and arguments and had the opportunity to share this at the Joint Annual Meeting with an engaged audience.